Answer:
![\textsf{Zeros}: \quad x=8, \quad x=2, \quad x=-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/xli8m272n00sg9tr67mz0bab99jtg7awoq.png)
Explanation:
Given function:
![f(x)=x^3-7x^2-14x+48](https://img.qammunity.org/2023/formulas/mathematics/high-school/klv8sksc6o48xmp7gqkeco1dx7uv0l7r76.png)
Factor Theorem
If f(x) is a polynomial, and f(a) = 0, then (x – a) is a factor of f(x).
Therefore, since f(8) = 0, then (x - 8) is a factor of the function f(x):
![\implies f(x)=(x-8)(ax^2+bx+c)](https://img.qammunity.org/2023/formulas/mathematics/high-school/1bx608oe4vtnlruyfp96goqp0hltz8bnbe.png)
The coefficient of x³ is a.
![\implies a=1](https://img.qammunity.org/2023/formulas/mathematics/high-school/xxyyi2ygmjise4a6sg565ds06g6nrrgia9.png)
The constant 48 is equal to -8c.
![\implies c=-6](https://img.qammunity.org/2023/formulas/mathematics/high-school/6444gzhwp6iyf2ocoeb0e5qggks3vk2p9z.png)
To find the value of b:
![\implies cx - 8bx = -14x](https://img.qammunity.org/2023/formulas/mathematics/high-school/tyywgwkstmkyi7vh2ws9l41os27na8u9uf.png)
![\implies -6-8b=-14](https://img.qammunity.org/2023/formulas/mathematics/high-school/4imlzpogdxqegz5ujd2pnjn3qozt1l7g3a.png)
![\implies -8b=-8](https://img.qammunity.org/2023/formulas/mathematics/high-school/lr7uh6mv95tl6v1a3apv2fbk9qz4g7xoc5.png)
![\implies b=1](https://img.qammunity.org/2023/formulas/mathematics/high-school/lvbt9nt3xng1t36khdrzuy14dc7bdx5mpv.png)
Therefore:
![\implies f(x)=(x-8)(x^2+x-6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/zeb6x0iaigoo22elvwgn1gigrb1yy20a7u.png)
Factor (x² + x - 6):
![\implies x^2+3x-2x-6](https://img.qammunity.org/2023/formulas/mathematics/high-school/w6bbxa9mp2xzkhd39l4vw303j9qu614xci.png)
![\implies x(x+3)-2(x+3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/b969m43vge0rjrhxvtobr6n229gewu1z0g.png)
![\implies (x-2)(x+3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vehq00k2n7srjiupex5qk0tqzfqirxdx3e.png)
Therefore the fully factored function is:
![\implies f(x)=(x-8)(x-2)(x+3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/8iqgmnpelmdrehwyt7hvdravzi3cqzx6xo.png)
To find the zeros of the function, set each factor to zero:
![\implies x-8=0 \implies x=8](https://img.qammunity.org/2023/formulas/mathematics/high-school/xpev6vojdmuf0o13nzfqqd48spcgxybnfd.png)
![\implies x-2=0 \implies x=2](https://img.qammunity.org/2023/formulas/mathematics/high-school/d0yipo604i7t7mkf1whclttc1p448vo21u.png)
![\implies x+3=0 \implies x=-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/slxt721lcflhsarta6oaxao8nd6p7rg9bw.png)